Exact and numerical solutions of generalized Drinfeld-Sokolov equations - Ugurlu, Yavuz; Kaya, Dogan (Elsevier Science Bv, 2008)
In this Letter, we consider a system of generalized Drinfeld-Sokolov (gDS) equations which models one-dimensional nonlinear wave processes in two-component media. We find some exact solutions of gDS by using tanh function method and we also obtain a numerical solution by using the Adomian's Decomposition Method (ADM). (C) 2008 Elsevier B.V. All rights reserved.
Keywords: generalized Drinfeld-Sokolov equations; tanh function method; Adomian's decomposition method; exact traveling wave solutions; numerical solutions